On the in vitro neutralization test of Clostridium perfringens type A toxin - Shemanova, G F; Vlasova, E V; Postnikova, T M (Journal of hygiene, epidemiology, microbiology, and immunology, 1988)
Data are presented on the detection in crude animal and human sera of Cl. perfringens phospholipase C (PLC) inhibitor. When the level of Cl. perfringens type A antitoxin is determined in the in vitro toxin neutralization test the inhibitor is found to decrease PLC activity in the test dose of experimental homologous toxin. The extent of decrease accounts for the variation of results obtained in the in vitro and in vivo toxin neutralization tests. The variation may be cancelled out by introducing a corresponding coefficient to calculate the level of alpha-antitoxin. It is suggested that the isolation and investigation of the PLC inhibitor will contribute to the development of preparations for treatment of gas gangrene due to Cl. perfringens type A.
Keywords: fosfolipasy typu C; bakteriální toxiny; Animals; Type C Phospholipases; Humans; neutralizační testy; lidé; zvířata; Antitoxins; antitoxiny; proteiny vázající vápník; Neutralization Tests; Bacterial Toxins; Clostridium perfringens; Calcium-Binding Proteins